2018
DOI: 10.5694/mja18.00199
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Oncology Society of Australia position statement on exercise in cancer care

Abstract: Clinical research has established exercise as a safe and effective intervention to counteract the adverse physical and psychological effects of cancer and its treatment. This article summarises the position of the Clinical Oncology Society of Australia (COSA) on the role of exercise in cancer care, taking into account the strengths and limitations of the evidence base. It provides guidance for all health professionals involved in the care of people with cancer about integrating exercise into routine cancer car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
244
1
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(266 citation statements)
references
References 40 publications
4
244
1
17
Order By: Relevance
“…To date, very few studies have used elements of EIM in the oncology care setting, but there is ample scope and a need to examine integration into cancer care. The evidence base strongly supports adoption of the EIM approach for all patients with chronic conditions, including people living with and beyond cancer . Therefore, we propose the EIM approach as a way forward in the oncology setting.…”
Section: What Oncology Clinicians Can Do Now: Assess Advise and Refermentioning
confidence: 95%
See 2 more Smart Citations
“…To date, very few studies have used elements of EIM in the oncology care setting, but there is ample scope and a need to examine integration into cancer care. The evidence base strongly supports adoption of the EIM approach for all patients with chronic conditions, including people living with and beyond cancer . Therefore, we propose the EIM approach as a way forward in the oncology setting.…”
Section: What Oncology Clinicians Can Do Now: Assess Advise and Refermentioning
confidence: 95%
“…The current article, the third in this triad, identifies and uses elements from the ACSM's Exercise Is Medicine (EIM) initiative to propose solutions to overcoming barriers to exercise referrals by oncology clinicians …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Randomized controlled trials have strengthened the foundation in efficacy data for exercise in oncology; however, experimental designs can lack generalizability to a clinical setting (eg, homogeneity of the sample, exclusion of comorbid conditions, or willingness to be randomized). [1][2][3] Randomized controlled trials have strengthened the foundation in efficacy data for exercise in oncology; however, experimental designs can lack generalizability to a clinical setting (eg, homogeneity of the sample, exclusion of comorbid conditions, or willingness to be randomized).…”
Section: Introductionmentioning
confidence: 99%
“…Specific exercise recommendations for men with prostate cancer on androgen deprivation therapy exist in the United Kingdom . The United States also have physical activity and nutrition guidelines for cancer survivors, and the Clinical Oncology Society of Australia recommends that exercise is embedded as an adjunct to therapy . Nevertheless, studies using self‐reported and accelerometry assessed physical activity suggest that the majority of men living with prostate cancer remain inactive, with less than 23% reaching recommended levels and levels of obesity rising after treatment …”
Section: Introductionmentioning
confidence: 99%